(untitled) (Research, Society and Development, 2024)
The remote teaching-learning process in the Baccalaureate of Pharmacy at UFMG brought many challenges to the students, thus our objective was to assess the satisfaction of the students with the ERL. It was evaluated when the classes were instituted by means of Emergency Remote Learning (ERL), during the coronavirus pandemic (SARS-CoV-2). A questionnaire addressing teaching-learning data, sociodemographic habits and lifestyle was collected through a virtual platform and, data are analyzed by linear regression and by the Classification And Regression Tree (CART) technique. The overall mean students´ satisfaction with ERL was 3.12±1.10 (Likert scale 1-5), presenting an inverse correlation with learning in the professional cycle of the course (p<0.001). Only 3.1% indicated ’none or little learned’, variable classified as maximum satisfaction. Low satisfaction was registered with the quality of the practical classes (3.06±1.22) revealing the limitation of ERL in the case of a lot of practical content, as for Pharmacy course. A high level of satisfaction was related to the didactics and methodology of the professors (3.55±0.99), showing their commitment and dedication to the ERL, despite the difficulties of its implementation. The study results point for improvements in content, course organization, or the use of different technologies to enhance student satisfaction with remote learning format.